Investigação da flotação por ar dissolvido no tratamento de efluente de lavanderia industrial utilizando coagulante de fonte renovável tanino - Thompson Júnior, José Pedro (2013)
This work investigated the technique of flotation by dissolved air for effluent treatment generated by Industrial Laundries. Effluents from industrial laundries, as a whole, contain dirt removed from clothes, outfits and IPE s, and substances added in the washing processes, which are normally treated in the coagulation/flocculation and sedimentation physical-chemical processes. In this work, bench tests were made aimed at finding an optimized methodology for the formation of flakes in the coagulation/flocculation phases with formats and densities suitable for the separation of sludge by flotation by dissolved air into an effluent from an industrial laundry. The tests were made in a jar test\" equipment with jars adapted for injection of saturated water, using tannins as coagulating agent and anionic polyelectrolyte as flocculating agent. This methodology also searched to improve the solid-liquid separation phase by using flotation by dissolved air, a not very common alternative for this type of effluent (high concentration of solids). The best results of turbidity removal were obtained with 400 ppm of Aluminum Sulphate and 770 ppm of Tanfloc SL, with 1.5 and 2.9 NTU, or removal efficiency of 99.9% and 99.7%, respectively. This work investigated the production conditions of air saturated water, by varying the saturation pressures at 2.5, 4.0, and 5.0 Kg/cm2, by varying the surfactant concentration Sodium Dodecyl Sulphate in air saturated water at 0, 10, 20 ppm. The control parameters were: volume of formed sludge, turbidity indexes of the treated effluent and solid-liquid separation time. The results shown in the tests with saturated water with pressures adjusted at 4.0 Kgf/cm2 and 5.0 Kgf/cm2 were the best ones on all parameters seen in this phase, with the transportation capacity of the sludge to the jar surface, the stability, and sludge volume (settling or compaction). As regards the saturated water production, the lowest turbidity indexes and formed sludge volume were obtained when 10 ppm and 20 ppm of surfactant Sodium Dodecyl Sulphate were added in the saturated water, pressure set at 2.5 Kgf/cm2 and applied at the proportion of 17.5% (saturated water/effluent). It was also observed that in the solid/liquid separation phase via flotation by dissolved water turbidity removals were obtained at the range of 99.8% and 99.7% for the coagulants, Aluminum Sulphate (inorganic) and cationic tannin (biodegradable organic), respectively. As regards the separation time, the FDA presented lower separation times for both coagulants, as compared with conventional decantation.